2004
DOI: 10.5483/bmbrep.2004.37.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Raw Starch Granules by α-Amylase Purified from Culture of Aspergillus awamori KT-11

Abstract: Raw-starch-digesting α-amylase (Amyl III) was purified to an electrophoretically pure state from the extract of a koji culture of Aspergillus awamori KT-11 using wheat bran in the medium. The purified Amyl III digested not only soluble starch but also raw corn starch. The major products from the raw starch using Amyl III were maltotriose and maltose, although a small amount of glucose was produced. Amyl III acted on all raw starch granules that it has been tested on. However, it was considered that the action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
(11 reference statements)
2
24
0
Order By: Relevance
“…This leads to physical disintegration of structure and consequent exposure of new sites susceptible to either or both enzymes. Most common synergies are completed by endo-and exo-acting RSDE [12,26,36,91]. Synergic action also has been reported for two endo-RSDEs: salivary α-amylase and pullulanase [92].…”
Section: Synergistic Effect Of Different Types Of Rsdementioning
confidence: 92%
See 1 more Smart Citation
“…This leads to physical disintegration of structure and consequent exposure of new sites susceptible to either or both enzymes. Most common synergies are completed by endo-and exo-acting RSDE [12,26,36,91]. Synergic action also has been reported for two endo-RSDEs: salivary α-amylase and pullulanase [92].…”
Section: Synergistic Effect Of Different Types Of Rsdementioning
confidence: 92%
“…This process is energy-intensive, thus Aspergillus awamori -- [8] Aspergillus awamori var. kawachi -- [9][10][11] Aspergillus awamori KT-11 air α [12] Aspergillus carbonarius rotten cassava β [13] Aspergillus cinnamomeus -GA [14] Aspergillus ficum -α [15] Aspergillus niger -GA [16,17] Aspergillus niger Cassava waste - [18] Aspergillus niger AM07 Soil α, GA [19] Aspergillus niger NIAB 280 -GA [20] Aspergillus niger sl. 1 Soil - [21] Aspergillus oryzae -GA [22] Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, filamentous fungi from the genera Aspergillus and Penicillium are among the most studied producers of rawstarch degrading amylases [17,18], as well as amylases that could act at relatively mild conditions [19]. Furthermore, species from these genera have been also described for their ability to produce accessory hydrolases [20][21][22][23].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, starch enzymatic hydrolysis is characterized by a high reaction rate. Moreover, several studies were reported on the hydrolysis on starches from tropical tubers and roots (Valetudie et al,1993;Adebiyi et al, 2005;Omemu et al, 2005) and cereals (colonna et al, 1988;Matsubara et al, 2004) . In addition to hydrolysis reactions, some α-amylases as many other glycosyl hydrolases also catalyse various types of transglycosylation reactions.…”
Section: Introductionmentioning
confidence: 99%